APPLICATION OF REMOTE SENSING IN THE STUDY OF MONSOON ENERGETICS OVER BAY OF BENGAL DURING SUMMER MONSOON - GOSWAMI , V. K.; SIKDAR , D. N. (MAUSAM, 1994)
I I AR ~ , rR;\CT All attempt has been made 10 slUd )' tho roon soon c ne rgeucs over Bil)' of Hengal by stu, lying th e cloud and monsoon depression field s during sum mer monsoon using 11 ROS ·N sa telli te ima ge ri es . Th e i UU h Pa kinetic ft amn-s. ,-.g . vergen ce. vortic ity and vertical vclochics fur Hfcw selected ph ases in th e Ray ufHen gal .luring 27 JUll("-6 Allgn ..l l Q"7lj within the 10° X Ill o grid box (it" . IS-!5 °N & ~5 0 95 ° E ) wt're computed. Next. th e kinematic Ieamres o f n rypi cul disturbed phase (5-7 Jul y 1979) we re studied in a Lagrangian frame by using drop wind so n' le dnm of 1 S n"!'ic;lr..: h ai rcrutt. The data profiles II a nd I' him:' been drawn 10 idemit'y the evolutiona ry femll~ ." of fin associau- I 111 1111 snnn depression. Fol lr wing Such ruau rr 111 ( I ~77) and the cln ud d lls l" r ~ltJ.t ics of (jnsw:uui t." nt , (I 'J9U): th l"wo plausible lIlod els of Il1ntt s tlon dL'p lr ..."i n l1 hil\"l' been posmhued in lerms of C lusl er ClJ ~ l eSl.:e n ..:e Theory (CCn and Ginn! e lu sler nl ~lr)· (( iCl"! The '(" nl en l 1l1 11. ~' d rClllntiuns 'Ailhin an ll a ruun,t Ihe lllunsuon d lopres..,iol1 wcn.- inl l.-ne,l hy making ll ~e of Gt }F.S im a!:l' l·l ·il-" Th " kinemal ic stud ies have rew ala l that th e h ighe r vH lues of \'ertical veloci ties , posi ti\ 'c \·.. r1icily lind \'t'll.l' C" '11.'1' c n lT,,~p h ll d w jlll lhe max imuUl cooncct in ' cloud ..:o\'e rllge 1';SoO-\'; .f fClnuing and mntu re stages ormo nSlll lll d C")lll' , !, icl11